'Back to the Future' in a Ukrainian Manner: Examining the Impact of the Contradictory 2001 and 2010 Education Reforms on Ukrainian Schools and Science Subjects. (June 2014) - Fomichova, Kseniya; Kazama, Futaba; Misonou, Taku
This study analyses and evaluates the impact of two recent (2001 and 2010) education reforms on Ukrainian secondary schools, and, in particular, on science subjects (physics, chemistry, biology and Earth science), in terms of the structural, quantitative and qualitative characteristics of the reformed disciplines. It also examines societal attitudes towards the changes introduced in education and explains the reasons behind them. The 2001 reform prescribed a gradual shift from a 10- or 11-year school system to a 12-year one as a measure needed for the integration of Ukraine into the European Higher Education Area according to the Bologna Process. The first graduates of the new course of study would have completed it in 2013. However, the reform implementation was interrupted on 6 July 2010, when the newly elected president signed Law 2442–17, which became a starting point for the 2010 reform enacting the return to 11 years of study. Both reforms were politically charged and met with a mainly negative attitude by the general population, which was particularly evident in the responses of teachers who considered certain key aspects of the 2001 and 2010 reforms to be an unnecessary political interference in an otherwise effective model of schooling.